A case study on customs trade facilitation at Zambia's Kasumbalesa border post - Mfune, Moses Lameck (GSB: Faculty, 2016)
The expansion of global trade, especially trade in intermediate products, compels goods to cross borders multiple times before assembly. This phenomena requires better trade facilitation mechanisms in conveyancing goods and people across borders. The World Customs Organization, among many other organizations, has been in the fore-front of promoting these trade facilitation techniques. This qualitative case study has an objective of analyzing the current trade facilitation techniques used at Kasumbalesa. It also aims at pointing out any outdated customs procedures. During the study, data was collected using questionnaires and oral interviews. Secondary data was also collected from publications of the World Customs Organization, World Bank and the World Trade Organization, among other sources. In addition, observational methods were also used to collect data. The case study focuses on Kasumbalesa as a representative entry/exit point in Zambia. Consequently, identification of challenges faced by goods and people crossing Kasumbalesa can help streamline operations at other Zambian borders.